Análisis de los estados financieros y su influencia en la toma de decisiones sobre la situación económica-financiera de la empresa Industria Textil Piura S.A.A en el año 2017 - Ventura Chamochumbi, Kevin Orlando (2019)
The present research, descriptive and inductive-deductive, was conducted in the company Textile Industry Piura SA, Piura-Peru, from August to December 2017, with the objective of determining the influence of the Analysis of Financial Statements in the economy – financial decision making of the company Industria Textil Piura SA in the year 2017. The sample consisted of the economic and financial information of the company for the period 2015-2016. The influence of the Analysis of the Financial Statements in the economic and financial decisionmaking of the company Industria Textil Piura S.A was determined. The analysis of the financial statements allows to make objective decisions about the economic and financial situation of the company. It is a transcendent tool that identifies potential problems allowing the management to perform with dynamism to ensure compliance with the company's objectives.